Lamivudine resistance leading to de novo hepatitis B infection in recipients of hepatitis B core antibody positive liver allografts. Issue 12 (11th November 2013) - Leong, Jennifer; Coty, Patrick; Fiel, M. Isabel; Chang, Charissa; Florman, Sander; Schiano, Thomas
Abstract : Most studies have shown that lamivudine (LAM) prophylaxis is sufficient to prevent hepatitis B virus (HBV) transmission in recipients of hepatitis B core antibody positive (HBcAb + ) allografts. However, de novo hepatitis B (DNHB) is known to occur in this patient population. Herein, we report a case series of four liver transplant recipients who developed DNHB after receiving HBcAb + allografts due to acquisition of LAM resistance mutations, suggesting that LAM prophylaxis may be suboptimal. A retrospective chart review was performed of all adult liver transplants performed at Mount Sinai from 2001 to 2010. A total of 79 patients received HBcAb + allografts for non‐hepatitis B‐related liver disease. Of these 79 recipients, four patients developed DNHB and were found to have documented LAM resistance. With the increasing use of HBcAb + donor livers, we suspect that there will also be a growing number of cases of DNHB due to acquisition of LAM resistance. We suggest that other agents, such as entecavir or tenofovir, be considered for use as prophylaxis in this patient population to decrease this risk.